Agronomic performance of strawberry varieties with potential for cultivation on the northern plateau of Santa Catarina state - Demetrio, Kelly Eduarda; Farias, Eduardo Virmond Souza; Steidel, Otávio Frederico Tschoeke; Palinguer, Rodrigo; Wisniewski, Caroline de Souza; Würz, Douglas André (Revista de Ciências Agroveterinárias, 2025)
The evaluation of cultivars to be planted in a region is an important tool for producers to make decisions regarding the replacement of old materials. In this context, the aim is to evaluate the adaptation of new varieties of strawberry for the Planalto Norte of Santa Catarina, to be able to indicate them to producers in the region. The experiment was set up on a rural property in the municipality of Canoinhas, Santa Catarina. The varieties evaluated were Pircinque, Beauty, Sunsation and Brilliance. The design used was randomized blocks, with four repetition and each experimental unit containing 30 plants. The following were evaluated: production (g/plant), yield (t/hectare), fresh fruit mass (g/fruit), fruit diameter and height (mm), % of commercial fruit, % of deformed fruit, % of small fruit, as well as physical and chemical evaluations: soluble solids (°Brix), total acidity (% citric acid), ratio (SS/AT), fruit firmness (kgf). The data was submitted to the variance test (ANOVA) and the means were then submitted to the Tukey test at a 5% probability of error. The Pircinque variety can be recommended for cultivation in the Planalto Norte Catarinense region, by presenting high productive indices, high soluble solid and Ratio, in addition to presenting greater fruit firmness, enabling greater post-harvest conservation. Beauty could also be an alternative for diversifying the varieties grown in the region, as it has good yields and ripens well for strawberry cultivation.